GIS-material for the archaeological project: Agricultural remains and Stone Age settlement in Södra Freberga - Double-track railway Motala-Norrsten - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned construction of a double track railway and flyovers between Motala and Norrsten, a new location for an existing rich fen and a new walk and cycle path, a 900 m2 big area was excavated in Södra Freberga. A field evaluation north of the railway track was performed in 1999, revealing agricultural layers and a microblade. This led to the excavation of area 1 (RAÄ 93), where agricultural layers were documented, and to a field evaluation of area 2, where it was verified that the planned development was not going to affect the archaeological remains. A third area south of the railway track was also evaluated. Here a Stone Age settlement was discovered.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the excavation was to document and determine the character of the agricultural layers within area 1 (RAÄ 93) before removing them. The purpose of the field evaluations was to determine the extent, type and dating of the ancient monuments within area 2, located nearby the remnants RAÄ 40:2 and 40:3, and within the area of remnant RAÄ 93.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Med anledning av det planerade dubbelspåret och planskilda korsningar utmed sträckan Motala - Norrsten och inom planerat område för ny plats för befintligt kalkkärr samt inom område för gång- och cykelväg har en sammantaget 900 m2 stor yta undersökts inom Södra Freberga. Området norr om järnvägsspåret förundersöktes 1999 och då påträffades odlingslager och fynd av ett mikrospån i flinta. Detta föranledde slutundersökningen av område 1 (RAÄ 93) där befintliga agrara lämningar togs bort efter dokumentation, samt en förundersökning av område 2 där det kunde konstateras att kommande arbetsföretag inte skulle komma i konflikt med lagskyddad fornlämning. Även ett tredje område söder om järnvägsspåret kom nu att förundersökas och här påträffades en boplats från stenåldern.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska slutundersökningen var att klargöra karaktären på och dokumentera de odlingslämningar som fanns inom område 1 (RAÄ 93) innan de schaktades bort. Syftet med förundersökningarna var att undersöka utbredning, typ och ålder på fornlämningarna inom område 2, som låg i närheten av RAÄ 40:2 och 40:3, och område 3, som låg inom fornlämningsområdet tillhörande RAÄ 93.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Odlingslämningar och stenåldersboplats i Södra Freberga - Dubbelspår Motala-Norrsten
Keywords: stone age; stenålder; historical period; historisk tid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi